Dantaswasthya in Ayurveda w.s.r. to Dantadhavan - Payal Sharma; Bhavika M. Dangar; Avanish Shukla (AYUSHDHARA, 2025)
In modern life, faulty lifestyles and poor dietary habits have led to a significant rise in oral diseases. Where Ayurveda science’s Prayojana- “Swasthasya Swasthya Rakshanam” emphasizing the importance of maintaining health. The Ayurvedic daily regimen or Dinacharya, provides detailed guidelines for promoting oro-dental health, including the practice of Dantadhavan (tooth cleaning). Various herbs recommended by different Acharyas play a crucial role in Dantadhavan, while some Acharyas also list herbs that should be avoided. This paper aims to explore various Ayurvedic herbs to promote orodental health and prevent various common orodental problems. Various tooth brushing and flossing techniques are mentioned separately in today’s practice, but these methods only emphasize on cleaning of teeth, on the contrary Danta dhawan dravyas don’t clean not only the oral cavity but also aids their medicinal properties to prevent diseases.